2013
DOI: 10.3111/13696998.2013.774279
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden associated with skeletal-related events in patients with bone metastases secondary to solid tumors in Belgium

Abstract: SREs add a substantial cost to the management of patients with bone metastases. Avoiding SREs can lead to important cost-savings for the healthcare payer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Bone complications are associated with decreased survival and considerable morbidity, pain, impaired mobility, and decreased quality-of-life 3,[5][6][7][8][9][10] . Healthcare costs for patients with bone complications are substantial 3,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Bone complications are associated with decreased survival and considerable morbidity, pain, impaired mobility, and decreased quality-of-life 3,[5][6][7][8][9][10] . Healthcare costs for patients with bone complications are substantial 3,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported costs of surgery for spinal metastases, and figures vary widely: €15,267 for both inpatient care and outpatient follow up in a Belgian study using Diagnosis Related Groups (DRG) codes and national tariffs 8 , an average inpatient cost of £16,885 in a United Kingdom study with patient-level actual costs, 9 but an average of $50,098 for direct costs to the hospital for inpatient stays in a San Francisco study, 10 and an average total of €87,814 over a lifetime horizon in a Danish study. 11 Detailed cost-utility analyses comparing surgical versus non-surgical approaches were performed by three authors.…”
Section: Introductionmentioning
confidence: 99%
“…Further, BM can complicate patient treatment by necessitating targeted radiation or bone surgery . The presence of BM not only shortens the overall survival (OS) of these patients (median 6–12 months) , but also results in a significantly increased financial burden for patients and the healthcare system overall . Although primary bone tumors and BM have been extensively studied, the molecular differences between LUAD and BM remain largely unstudied.…”
Section: Introductionmentioning
confidence: 99%